Ecology and digital technologies. Small-scale architecture as a place of connections - Massimo Perriccioli; Roberto Ruggiero; Michael Salka (Agathón)
Starting from the relationships between digital technologies and environmental culture, the essay aims to outline the contours of the new ecological dimension of architectural design as a place of multiple and interacting connections in which we can critically resolve the dichotomy between nature and culture. From this point of view, small-scale architecture provides a promising field of experimentation in which new technological systems, marked by more efficient ecological solutions, meet and integrate with the management of biological cycles. Industrial and production processes, rethought on the basis of the circularity paradigm, can be organised in a similar way to natural ecosystems with regard to the use of energy and materials, becoming a promising option for making them more efficient and sustainable.